2021
DOI: 10.1038/s41467-021-26525-z
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of fungal biofilm development by extracellular vesicle cargo

Abstract: The fungal pathogen Candida albicans can form biofilms that protect it from drugs and the immune system. The biofilm cells release extracellular vesicles (EVs) that promote extracellular matrix formation and resistance to antifungal drugs. Here, we define functions for numerous EV cargo proteins in biofilm matrix assembly and drug resistance, as well as in fungal cell adhesion and dissemination. We use a machine-learning analysis of cargo proteomic data from mutants with EV production defects to identify 63 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 42 publications
3
48
0
3
Order By: Relevance
“…In the case of C. albicans biofilm, it has been shown that vesicles produced by cells in the biofilm contribute to the formation of the biofilm matrix and the occurrence of fluconazole resistance ( Zarnowski et al., 2018 ; Zarnowski et al., 2021 ). Therefore, in this study we examined whether EVs might influence formation of biofilm by C. tropicalis, which of the three tested Candida species produced the most stable biofilm and was susceptible to the applied antifungal drugs ‒ fluconazole (FLU) and caspofungin (CASP) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of C. albicans biofilm, it has been shown that vesicles produced by cells in the biofilm contribute to the formation of the biofilm matrix and the occurrence of fluconazole resistance ( Zarnowski et al., 2018 ; Zarnowski et al., 2021 ). Therefore, in this study we examined whether EVs might influence formation of biofilm by C. tropicalis, which of the three tested Candida species produced the most stable biofilm and was susceptible to the applied antifungal drugs ‒ fluconazole (FLU) and caspofungin (CASP) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…EVs and their content might participate in the interaction between fungal pathogens and human cells during infection development, inducing also immune system response ( Gil-Bona et al., 2015 ; de Toledo Martins et al., 2018 ). Moreover, Candida EVs might also play an important role in the communication between cells of the same species forming a complex community, influencing fungal cell adhesion to different surfaces, formation of biofilm structures, and further development and propagation of infection ( Zarnowski et al., 2018 ; Zarnowski et al., 2021 ). In addition, the communication through EV release between Candida yeasts and other microorganisms living in the same niche might be crucial in the development of multispecies infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and variety of the reported fungal EV cargo has increased lately with the interest to study these structures. EVs are likely to participate in cell wall remodeling ( Longo et al., 2014 ; Nimrichter et al., 2016 ; Zhao et al., 2019 ; reviewed in Rizzo et al., 2020 ) as well as in the synthesis of Candida biofilms ( Zarnowski et al., 2018 ; Zarnowski et al., 2021 ). They participate in the synthesis of the main virulence factor in Cryptococcus , which is the high molecular weight glucuronoxylomannose component of the capsule ( Rodrigues et al., 2008 ; Reis et al., 2019 ; reviewed in de Oliveira et al, 2020 ; Rizzo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes were once considered to be the waste products of cells in the original research. Nowadays, more and more studies have shown that exosomes play important roles in organisms, such as cell-to-cell communication ( Ruhland et al, 2020 ; Schneider et al, 2021 ), immune response ( Kalluri and LeBleu, 2020 ; Su et al, 2020 ), cell growth and differentiation ( Yin et al, 2021 ; Zarnowski et al, 2021 ), as well as molecular transport ( Zhu Q. et al, 2021 ). Crucially, the concentration and phenotype of exosomes have been proved to reflect the state of their parental cells and associate with the occurrence and development of various diseases, such as cancers ( Jiang et al, 2021 ), infectious diseases ( Ning et al, 2021 ; Xie et al, 2021 ), metabolic, and cardiovascular diseases ( Kalluri and LeBleu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%